The Influence of Polymers to the Oil-Water Separation in Liquid-Liquid Hydrocyclone - Ishak, K.E.H.K. (Springer, 2020)
Liquid-liquid hydrocyclone (LLHC) has been used in the produced water treatment system to remove oil contaminant. However, the efficiency of the LLHC for treating the produced water from polymer flooding is unknown. The objective of this study is to investigate and compare the effect of two polymers with different molecular weight (MW), DL-333, and GLP-100 in the oil-water separation by using LLHC. The efficiency of the LLHC was analyzed in term of the oil concentration presence at the underflow of the LLHC comparing to the oil concentration at the inlet. The other parameters involved in this study are the LLHC operating conditions, which are feed flowrate and split ratio. Synthetic produced water was created by mixing 1000Â ppm crude oil, 14000Â ppm brines and different types of polymers with the concentration ranging from 0â1000Â ppm. An ultrasonic mixer was used at 13000Â rpm for 10Â min to produce the synthetic produced water. A total of 34 experiments were designed by using Response Surface Methodology (RSM). The experiments were conducted, and the significance of the parameters was analyzed. Based on the ANOVA analysis, all parameters (polymer type, polymer concentration, feed flowrate, and split ratio) are significant in the process. The high MW of polymer (GLP-100) has decreased the efficiency of oil-water separation compared to the low MW of polymer (DL-333). Increasing the feed flowrate and split ratio had increased the efficiency of the LLHC. Two correlations for the efficiency prediction for GLP-100 and DL-333 respectively, were developed by using RSM. Â© 2020, Springer Nature Singapore Pte Ltd.